Repeated oral esketamine in patients with treatment resistant depression and comorbid posttraumatic stress disorder - J.K.E. Veraart; M. van Westenbrugge; J.E. van Wulfften Palthe; A. van der Meij; R.A. Schoevers; J. de Jong (Heliyon, 2023)
Introduction: Ketamine and its S-enantiomer esketamine are novel pharmacotherapeutic options for treatment resistant depression (TRD). There is growing evidence on the efficacy for other psychiatric disorders, including posttraumatic stress disorder (PTSD). It is hypothesized that psychotherapy may further potentiate the effects of (es)ketamine in psychiatric disorders. Methods: Repeated oral esketamine was prescribed once or twice weekly in five patients suffering from TRD and comorbid PTSD. We describe the clinical effects of esketamine and report data from psychometric instruments and patients’ perspectives. Results: Esketamine treatment duration ranged from six weeks to a year. In four patients, we observed improvement in depressive symptoms, increased resilience and more receptiveness to psychotherapy. One patient experienced symptom worsening in response to a threatening situation during esketamine treatment, highlighting the need for a safe setting. Discussion: (Es)ketamine treatment within a psychotherapeutic framework appears promising in patients with treatment resistant symptoms of depression and PTSD. Controlled trials are warranted to validate these results and to elucidate the optimal treatment methods.